STRATEGI â€œRUMAH BACA TERATAIâ€ UNTUK MEMBENTUK CITRA POSITIF MASYARAKAT DADAPSARI KELURAHAN SANGKRAH KOTA SURAKARTA - Siswanto, Caroline Tyas Wardhani & (Transformasi, 2016)
This study aims to determine the communication strategy undertaken by the Rumah BacaTeratai community in forming a positive image the society of Sangkrah especially Dadapsarivillage. Data collected from informants who know the problems facing the Dadapsari village.Subsequent data analysis was performed using the method of analysis componential after all thedata is ensured validity. Data validation was taken with the technique of triangulation of datasource. The results showed that the communication strategies used by the community of RumahBaca Teratai read that emphasizes direct communication that are informal in the planningdone, simple implementation and proven to yield positive response of society in general andcapable of forming a positive image of the Dadapsari village.Keyword: Communication Strategies and Positive Image